224k views
0 votes
A. Find an equation for F^-1 (x) the inverse function. B. Verify that your equation is correct by showing that (F ^-1 (x)) =x and f^-1 f(x))=x

A. Find an equation for F^-1 (x) the inverse function. B. Verify that your equation-example-1

1 Answer

2 votes

A)

Replace y=f(x), isolate x and then replace x=f^-1(y) to find the inverse function:


\begin{gathered} f(x)=x+7 \\ \Rightarrow y=x+7 \\ \Rightarrow y-7=x \\ \Rightarrow x=y-7 \\ \Rightarrow f^(-1)(y)=y-7 \\ \\ \therefore f^(-1)(x)=x-7 \end{gathered}

B)

Evaluate f at f^-1(x) and f^-1 at f(x):


\begin{gathered} f(f^(-1)(x))=f^(-1)(x)+7=x-7+7=x \\ f^(-1)(f(x))=f(x)-7=x+7-7=x \end{gathered}

Therefore, the answer is option A)


f^(-1)(x)=x-7\text{ for all x}

User Timeout
by
5.1k points